A Systematic Review and Meta-analysis of Randomized Controlled Trials Comparing Intraoperative Red Blood Cell Transfusion Strategies. Issue 3 (March 2022) - Lenet, Tori; Baker, Laura; Park, Lily; Vered, Michael; Zahrai, Amin; Shorr, Risa; Davis, Alexandra; McIsaac, Daniel I.; Tinmouth, Alan; Fergusson, Dean A.; Martel, Guillaume
Abstract : Objective: The objective of this work was to carry out a meta-analysis of RCTs comparing intraoperative RBC transfusion strategies to determine their impact on postoperative morbidity, mortality, and blood product use. Summary of Background Data: RBC transfusions are common in surgery and associated with widespread variability despite adjustment for casemix. Evidence-based recommendations guiding RBC transfusion in the operative setting are limited. Methods: The search strategy was adapted from a previous Cochrane Review. Electronic databases were searched from January 2016 to February 2021. Included studies from the previous Cochrane Review were considered for eligibility from before 2016. RCTs comparing intraoperative transfusion strategies were considered for inclusion. Co-primary outcomes were 30-day mortality and morbidity. Secondary outcomes included intraoperative and perioperative RBC transfusion. Meta-analysis was carried out using random-effects models. Results: Fourteen trials (8641 patients) were included. One cardiac surgery trial accounted for 56% of patients. There was no difference in 30-day mortality [relative risk (RR) 0.96, 95% confidence interval (CI) 0.71–1.29] and pooled postoperative morbidity among the studied outcomes when comparing restrictive and liberal protocols. Two trials reported worse composite outcomes with restrictive triggers. Intraoperative (RR 0.53, 95% CI 0.43–0.64) and perioperative (RR 0.70, 95% CI 0.62–0.79) blood transfusions were significantly lower in the restrictive group compared to the liberal group. Conclusions: Intraoperative restrictive transfusion strategies decreased perioperative transfusions without added postoperative morbidity and mortality in 12/14 trials. Two trials reported worse outcomes. Given trial design and generalizability limitations, uncertainty remains regarding the safety of broad application of restrictive transfusion triggers in the operating room. Trials specifically designed to address intraoperative transfusions are urgently needed. Abstract : Supplemental Digital Content is available in the text